2014
DOI: 10.3174/ajnr.a4142
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Diagnosis of Suprasellar Papillary Craniopharyngioma and Germ Cell Tumors of Adult Patients

Abstract: Younger age, diabetes insipidus, MR imaging characteristics of restricted diffusion, and vertical infundibular extension favor the diagnosis of germ cell tumors. Spheric shape without infundibular infiltration provides clues to papillary craniopharyngiomas, which originate from the pars tuberalis and are located outside the third ventricle. We suggest that suprasellar germ cell tumor is possibly an intraventricular lesion. Appropriate treatment planning can be initiated according to the diagnosis and anatomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Correct diagnosis of the papillary type is essential for planning the therapeutic strategy, particularly to prevent tumor biopsy for histological confirmation when surgery is discarded as a primary treatment option. Nevertheless, there is inconsistent information regarding the radiological characteristics of PCPs, possibly related to the low resolution of the neuroradiological studies performed before the 1990s and the usual inaccurate definition of the MRI findings [11,17,19,[71][72][73][74][75]. The first comparative study of MRI features differentiating PCPs from ACPs, performed by Sartoretti-Schefer et al [72], identified the predominantly solid consistency and rounded shape as the two major morphological characteristics of the papillary type, in contrast to the usual mixed-solid consistency and lobulated morphology of the adamantinomatous one.…”
Section: Pcp Diagnosis: Specific Mri Characteristicsmentioning
confidence: 99%
“…Correct diagnosis of the papillary type is essential for planning the therapeutic strategy, particularly to prevent tumor biopsy for histological confirmation when surgery is discarded as a primary treatment option. Nevertheless, there is inconsistent information regarding the radiological characteristics of PCPs, possibly related to the low resolution of the neuroradiological studies performed before the 1990s and the usual inaccurate definition of the MRI findings [11,17,19,[71][72][73][74][75]. The first comparative study of MRI features differentiating PCPs from ACPs, performed by Sartoretti-Schefer et al [72], identified the predominantly solid consistency and rounded shape as the two major morphological characteristics of the papillary type, in contrast to the usual mixed-solid consistency and lobulated morphology of the adamantinomatous one.…”
Section: Pcp Diagnosis: Specific Mri Characteristicsmentioning
confidence: 99%
“…e have read with great interest the original article by Lee et al, 1 "Pretreatment Diagnosis of Suprasellar Papillary Craniopharyngioma and Germ Cell Tumors of Adult Patients," recently published in the American Journal of Neuroradiology, which analyzes the MR imaging features of a series of 18 papillary craniopharyngiomas (PCPs), to achieve an accurate differential diagnosis between these lesions and the group of germ cell tumors involving the infundibulotuberal area. First and foremost, we would like to congratulate the authors for their thorough survey on such a challenging topographic variant of craniopharyngioma (CP), a topic rarely addressed in neuroradiologic research.…”
mentioning
confidence: 99%
“…Researches on MRI, the most important examination for intracranial tumors, have shown that some imaging characteristics could be considered significant in the diagnosis. For example, the imaging characteristic of germinoma component is solid, which is predominant with the heterogeneous enhancement of the solid portion on the contrast-enhanced T1WI, while CP is cystic, which is predominant with a marginal enhancement of the multi-cystic lesion [24]. Meanwhile, the apparent diffusion coefficient (ADC) of CP is usually higher than germinoma on diffusion-weighted imaging (DWI) sequences [25].…”
Section: Discussionmentioning
confidence: 99%